E. coli Strains in Iraq Show High Antibiotic Resistance and Virulence Potential: Strain E. coli di Irak Menunjukkan Resistensi Antibiotik yang Tinggi dan Potensi Virulensi - Farhood, Abeer Hadi; Muttlaq, Amena Lafeta; Khudair, Teeba T. (Academia Open, 2024)
General Background: Escherichia coli is a widely distributed species that includes strains ranging from highly pathogenic to harmless avirulent isolates, often found in the human gut. Specific Background: E. coli pathogenicity is determined by virulence factors like adhesins, invasins, toxins, and capsules, which are often transferred horizontally via phages and plasmids. Knowledge Gap: Despite advancements in understanding E. coli virulence, there is a need to further understand genetic factors contributing to urinary tract infections, especially in regions with high antibiotic resistance. Aims: The study investigated the prevalence of virulence genes and antibiotic resistance in E. coli strains from UTI patients at Al Hussien Teaching Hospital in Iraq. Results: The study reveals the presence of specific virulence genes in UPEC strains from a specific region, suggesting the potential involvement of the pap AH gene in UTI pathogenesis. Novelty: This study reports the prevalence of specific virulence genes in UPEC strains from a specific region, indicating the potential role of the pap AH gene in UTI pathogenesis. Implications: The study indicates that UPEC strains, characterized by high virulence factors like pap AH, are promising vaccine targets, necessitating further research for effective prevention strategies. Highlights: E. coli strains show high antibiotic resistance in UTI patients. pap AH gene is crucial for UPEC virulence. Virulence factors like pap AH are potential vaccine targets. Keywords: E. coli, UTI, virulence factors, antibiotic resistance, pap AH gene